1999
DOI: 10.1542/peds.103.5.e67
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma of the Urinary Bladder, Preclinically Detected by Mass Screening

Abstract: ABSTRACT. Background. Since the introduction of mass screening of infants for neuroblastoma, the incidence of neuroblastoma has increased in Japan. The reason for this increased incidence is the possible inclusion of many neuroblastomas that would have regressed spontaneously and would never have been detected clinically. An extremely rare tumor at the dome of the urinary bladder in a 7-month-old infant was detected by the mass screening.Methods. A case of neuroblastoma of the urinary bladder is reported with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…2 Only 6 previous cases of bladder NBL have been reported to date. [3][4][5][6][7] Two other cases presented with gross hematuria. 6,7 Of the remaining cases, 3 were asymptomatic, and detected as a result of a mass screening program, 4,5 and one case was discovered as a palpable mass on physical examination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2 Only 6 previous cases of bladder NBL have been reported to date. [3][4][5][6][7] Two other cases presented with gross hematuria. 6,7 Of the remaining cases, 3 were asymptomatic, and detected as a result of a mass screening program, 4,5 and one case was discovered as a palpable mass on physical examination.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 Of the remaining cases, 3 were asymptomatic, and detected as a result of a mass screening program, 4,5 and one case was discovered as a palpable mass on physical examination. 6 Five out of 6 reported cases of bladder NBL also occurred at the dome of the bladder, [3][4][5]7 with one tumour arising from the anterior bladder wall. 6 In four of the previously described cases, the patients underwent immediate partial cystectomy without neoadjuvant or adjuvant chemotherapy or radiation required.…”
Section: Discussionmentioning
confidence: 99%
“…They are characterized by the onset of chronic secretory diarrhea with hypokalemia, increased VIP values both in the blood and tumor as well as increased urinary catecholamine Key words: coeliac disease; ganglioneuroblastoma; childhood cancer ------Abbreviations: AGA, antigliadin antibody; AEA, antiendomysium antibody; hTG, antibodies to human tissue transglutaminase levels. The most frequent sites of such tumors in children are the adrenal medulla and the retroperitoneal paravertebral ganglia [3]. Bloom et al in 1973 reported increased VIP levels in adults with retroperitoneal ganglioneuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma of the urinary bladder is extremely unusual. We have reviewed the literature and found only three cases of neuroblastoma primarily located in the dome of the urinary bladder that have been reported [3][4][5]. Two of them were asymptomatic and were found only as a con-sequence of mass screening programs in Japan [4,5].…”
mentioning
confidence: 99%
“…We have reviewed the literature and found only three cases of neuroblastoma primarily located in the dome of the urinary bladder that have been reported [3][4][5]. Two of them were asymptomatic and were found only as a con-sequence of mass screening programs in Japan [4,5]. Certainly, rhabdomyosarcoma was the most likely clinical diagnosis based on the clinical signs and imaging studies because that soft tissue sarcoma frequently affects the genitourinary structures of the pelvis in both males and females.…”
mentioning
confidence: 99%